2012
DOI: 10.1111/ane.12000
|View full text |Cite
|
Sign up to set email alerts
|

Paraoxonase 1 activity in multiple sclerosis patients during mitoxantrone therapy

Abstract: Mitoxantrone therapy does not influence PON1 activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…It should be borne in mind that mitoxantrone is potentially associated with an increased level of OS but on the other hand, the study demonstrated that mitoxantrone did not have an effect on the activity of paraoxonase 1 (an enzyme that protects the cell from OS) [160]. …”
Section: The Relationship Between Immunomodulatory Therapy Os Anmentioning
confidence: 99%
“…It should be borne in mind that mitoxantrone is potentially associated with an increased level of OS but on the other hand, the study demonstrated that mitoxantrone did not have an effect on the activity of paraoxonase 1 (an enzyme that protects the cell from OS) [160]. …”
Section: The Relationship Between Immunomodulatory Therapy Os Anmentioning
confidence: 99%
“…Mitoxantrone has previously been shown to similarly induce oxidative stress of nucleated cells [8,86,87,88]. On the other hand, mitoxantrone may strengthen the antioxidative defence [89,90]. The latter effect presumably requires expression of the respective proteins, an effect not possible in erythrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…However, this increase was less significant compared with untreated RRMS patients or SPMS patients treated with mitoxantrone (103). It should be borne in mind that mitoxantrone is associated with an increased level of OS (104). On the other hand, the study demonstrated that mitoxantrone did not have an effect on the activity of paraoxonase 1 (a type of enzyme that protects cells from OS) (104).…”
Section: The Relationship Between Immunomodulatory Therapy Os and Amentioning
confidence: 99%